The importance of a standardized Islamic manufacturing (IMP) for food and pharmaceutical productions - Rahman Nasaruddin, Ricca; Mel, Maizirwan; Fuad, Faizah; Jaswir, Irwandi; Abd Hamid, Hamidon (2011)
As Muslims, the search for lawful (halal) and wholesome (tayyib) products such as food and medicines is not only a part of ibadah and to get pleasure of Allah SWT. In fact, it can also nourish the bodies and souls due to the permissibility and purity of the products. Currently, the awareness of some doubtful and questionable ingredients in the food and pharmaceutical products in the market has increased. Since the 23rd meeting of the Standing Committee for Economic and Commercial Cooperation (COMCEC) on November 2007, OIC has organized a conference and its sequential meeting on The OIC Halal Food Standard. Three main documents – OIC General Guidelines on Halal Food, Guidelines for Bodies Providing Halal Certification, and Guidelines for the Authorized Accreditation Body Accrediting Halal Certification Bodies – have been finalized. However, the concern is now wider and more complex in nature incorporating not only the traditional aspects but also the biopharmaceutical manufacturing processes and other relevant processes. Thus, there is an urgent need for a comprehensive guideline. The concept of Islamic Manufacturing Practice (IMP) has been introduced in Malaysia to fill this void but unfortunately, the contents of the IMP are still equivocal and limited. This paper discusses about some aspects of manufacturing processes in food and pharmaceutical industries that reflect the importance of a standardized IMP.